Inhibition of methane production in an alpine wetland of the Tibetan plateau by carbon-based nanomaterials - Chengfang Ma; Rong Wen; Miao Lin; Hongfei Chi; Meiling Feng; Pengfei Liu (Environmental Research, 2026)

Numerical study on the influence of mangrove density and belt width on wave attenuation characteristics under regular waves - Hongfei Mao; Junxian Teng; Jinbo Lin; Shuidi Yang; Guanglin Wu; Wei Wang; Ya Men (Ocean Engineering, 2026)

Polystyrene microplastics disrupt the blood-testis barrier via CEBPB-driven lysosomal autophagy and induce ferroptosis-like injury in human sperm, compromising embryo development - Man Wu; Lei Li; Tianxin Zhao; Yuling Mao; Jiajing Lin; Xiaomin Li; Yanling Bai; Feixue Han; Shuyan Chen; Tianwen Peng; Chen Liao; Xin Ye; et al. (Journal of Hazardous Materials, 2026)

Trophic transfer in a cold seep food web: Dual constraints from δ13C-δ15N isotopes and rare earth elements - Zice Jia; Niu Li; Xun Sun; Shamik Dasgupta; Shaomin Lin; Hongfei Lai; Wenhua Feng; Chao Zhong; Zenggui Kuang; Fang Chen (Deep Sea Research Part I: Oceanographic Research Papers, 2026)

ErbB4 in the Dorsolateral Prefrontal Cortex is Required for Sensory Gating and Working Memory in Monkey - Minzhe Yang; Yingying Han; Hongfei Zhang; Chaolin Ma; Lin Mei; Baoming Li (Neuroscience Bulletin, 2026)

Transport and retention mechanism of CdS nanoparticles in layered heterogeneous porous media: Coupled regulation of interfacial heterogeneity and ionic strength - Xiangru Liu; Xin Yang; Hongfei Du; Xiaoyang Yue; Shanshan Lin (Journal of Environmental Management, 2026)

Has rising bottom water temperature since the Last Glacial Maximum caused gas hydrate dissociation? - Cong Cheng; Tao Jiang; Zenggui Kuang; Zigui Chen; Jinfeng Ren; Hongfei Lai; Licheng Cao; Qianru Wang; Yipan Hu; Lin Song; Chen Liang; Xu Zhao; et al. (Global and Planetary Change, 2026)

Optimizing water and nitrogen management to balance yield and nitrogen loss in mechanically harvested low-stubble ratoon rice - Chaojie Lan; Hailong Xu; Bin Qin; Jinying Li; Bianhong Zhang; Jingnan Zou; Ting Chen; Jiahui Song; Zhihan Chen; Changxun Fang; Zhixing Zhang; Hongfei Chen; et al. (Field Crops Research, 2026)

Cross-scale synergistic detoxification mechanisms of electric field in alleviating the inhibitory effects of oxytetracycline on anammox consortia - Hongfei Du; Xinlong Wang; Xiangru Liu; Xin Yang; Xiaoyang Yue; Shanshan Lin; Dandan Zhou (Water Research, 2026)

Numerical investigation of structural dimension effects on the extreme wave attenuation characteristics of floating breakwaters - Jinbo Lin; Ziyu Zhu; Yang Liu; Hongfei Mao; Yingchao Ma; Hui Yang; Zhenglin Tian (Ocean Engineering, 2026)

Significantly improved antibiotics removal and material utilization in novel electrodialysis integrated with nanostructured carbon microspheres - Xincheng Ji; Haoming Chen; Hongfei Zhang; Yuanming Guo; Jizhong Meng; Xinmin Zhan; Liwen Xiao; Lin Shi (Water Research, 2025)

Higher-harmonic resonance response of a monopile-supported offshore wind turbine in waves and wind - Hui Yang; Yi Zhang; Jinbo Lin; Hongfei Mao (Ocean Engineering, 2025)

Machine learning-guided multi-objective optimization for selective lithium extraction and valuable metal reuse from spent lithium-ion batteries - Jiayi Qu; Boge Zhang; Ronghua Jiang; Jun Huang; Mingjie Li; Sicheng Zheng; Wenjing Yu; Pengxin Sun; Yihua Xu; Yanping Hou; Hongfei Lin; Zebin Yu (Chemical Engineering Journal, 2025)

Numerical study of wave heights impact on the extreme wave attenuation characteristics of plants - Jinbo Lin; Runzhen Wu; Yanli He; Hui Yang; Yang Liu; Hongfei Mao; Guanglin Wu (Ocean Engineering, 2025)

Mechanisms of high yield formation and carbon budget surplus in ratoon rice and its rhizosphere microecological responses - Jinying Li; Hailong Xu; Bin Qin; Bianhong Zhang; Mengying Chen; Peiying Weng; Chunlin Guo; Chaojie Lan; Jingnan Zou; Zhimin Lin; Wenfang Lin; Wenfei Wang; et al. (Field Crops Research, 2025)

In situ construction of vertical carbon nanosheets on carbon fibers toward high-performance epoxy composites via interfacial enhancement - Na Sun; Bicheng Lin; Quanqing Cui; Qi Zheng; Lu Liu; Chuanshen Wang; Hongliang Ding; Hongfei He; Keqing Zhou; Wei Yang; Bin Yu (Chemical Engineering Journal, 2025)

Inspecting urban transit-oriented development from the perspective of human activity: A case study of Xi'an, China - Jiayu Liu; Xiping Yang; Lin Luo; Junyi Li; Hongfei Chen; Rui An; Jiyuan Li (Journal of Transport Geography, 2025)

Preparation of MCM-22/ZSM-5 core–shell structured zeolite for catalytic cracking of polyethylene to selectively produce paraxylene - Hucheng Ge; Yufei Gu; Feifei Liu; Yanmei Huang; Yuke Liu; Silin Wu; Yunshuang Hu; Zhixia Li; Hongfei Lin (Fuel, 2025)

IoT-enabled hierarchical thermoelectric nanocomposites for adaptive fire safety systems: Self-powered sensing and threshold-tunable alerts - Chuanshen Wang; Haorui Dun; Lu Liu; Hongliang Ding; Hongfei He; Bicheng Lin; Wenyu Hu; Na Sun; Yuan Hu; Bin Yu (Chemical Engineering Journal, 2025)

Demethoxycurcumin induces metabolic crisis and ATF4/ATF3/CHOP-dependent cell death in hepatocellular carcinoma - Fugen Shangguan; Hongfei Zhou; Huachang Zhang; Thaiyuri Reddy; Mhaka Panashe Bryan; Ri Cui; Jianhu Lin; Yongping Chen; Yihu Zheng (Chemico-Biological Interactions, 2025)

Evaluating the sustainability potential of perennial rice in southeastern China by comparing yield, environmental impacts and economic benefits - Hailong Xu; Bianhong Zhang; Bin Qin; Jinying Li; Chaojie Lan; Jingnan Zou; Yazhou Liu; Chunlin Guo; Zhimin Lin; Qiaohong Fan; Changxun Fang; Zhixing Zhang; et al. (Agriculture, Ecosystems & Environment, 2025)

Influence of Interspecies Interactions on Bacterial Community Assembly in the Active and Permafrost Layers on the Qinghai-Tibet Plateau - Hongfei Chi; Xiufeng Yin; Xuefeng Zhang; Jingyi Zhu; Lin Zhao; Yongcui Deng; Pengfei Liu; Yongqin Liu (Journal of Earth Science, 2025)

Rhizosphere microecological mechanism of carbon sequestration and its emission mitigation in rice ratooning - Jinying Li; Bin Qin; Chaojie Lan; Hailong Xu; Jingnan Zou; Bianhong Zhang; Changxun Fang; Zhixing Zhang; Hongfei Chen; Wenxiong Lin (Agriculture, Ecosystems & Environment, 2025)

Effective denitrification from landfill leachate using magnetic PVA/CMC/DE carrier immobilized microorganisms - Yunshuang Hu; Yufei Gu; Jiahui Tan; Chong Ding; Xinyi Yu; Zhixia Li; Hongfei Lin (Waste Management, 2025)

Study on the influence of submergence depth on the hydrodynamic and wave load characteristics of semi-submersible structures induced by a solitary wave - Jinbo Lin; Runzhen Wu; Yanli He; Yingchao Ma; Zhongbing Zhou; Yang Liu; Hongfei Mao; Guanglin Wu (Frontiers in Marine Science, 2024)
The submergence depth directly affects the safety of semi-submersible marine structures due to that the submergence depth significantly impacts on the hydrodynamic characteristics and wave loads of structures excited by extreme wave. This paper studies the influence of submergence depth on the hydrodynamic and wave load characteristics of semi-submersible structures by establishing a numerical model of the interaction between solitary waves and semi-submersible structures based on the SPH model and Rayleigh theory. Furthermore, equations for transmission coefficient, reflection coefficient, and wave load are fitted. The calculated wave heights of solitary wave propagation test case are in good agreement with the theoretical values. The maximum relative error of the wave peak is 8.4%. The calculated wave loads of submerged horizontal plates test case has a consistent trend with the experimental data. The maximum relative error of wave load peak and valley is 54% (absolute error 0.37 N). Furthermore, the interaction between solitary waves and structures with different submergence depths is investigated by using the meshless numerical model. It is found that the reflection coefficient first increases and then decreases with increasing submergence depth, and reaching a maximum value of 0.39 at the submergence depth equal to 0.0 m. On the contrary, the transmission coefficient decreases first and then increases with the increase of submergence depth. The minimum value of transmission coefficient is 0.36 with the submergence depth of 0.3 m. As the submergence depth increased, the horizontal wave load peak of the structure gradually increases, and the maximum value of 0.13 is obtained at the submergence depth of 0.7 m. The peak of vertical wave load rapidly increases with the increase of submergence depth and then gradually decreases while the trough gradually decreases with increasing submergence depth.

Pt/MgO catalysts intrinsically promoted by fast moving bed pyrolysis for hydrogenation properties - Hao Zhang; Hongfei Lin; Ziyue Wang; Liyang Liu; Hao Liu; Xiaohui He; Hongbing Ji (Chemical Engineering Journal, 2024)

Laboratory study of energy transformation characteristics in breaking wave groups - Guanglin Wu; Yanli He; Yizhe Zhang; Jinbo Lin; Hongfei Mao (Frontiers in Marine Science, 2024)
The spilling-breaking waves that appear in chirped wave packets are studied in a two-dimensional wave channel. These waves are produced by superposing waves with gradually decreasing frequencies. The analysis focuses on the nonlinear characteristics, energy variation, and energy transformation during the evolution and breaking of wave groups. Ensemble empirical mode decomposition is used to analyze the non-breaking and breaking energy variations of the intrinsic mode functions (IMFs). It is found that the third-order IMF component is a source of non-breaking energy dissipation and the second-order IMF, which represents a short wave group with a relatively higher energy content, is a primary source of the energy loss caused by wave breaking. Additionally, the findings reveal that among the three waves preceding the maximum crest, the wave closest to the maximum crest carried most of the energy. When wave breaking occurs, the energy dissipation caused by the wave breaking primarily originates from that wave. After wave breaking, whether it is the first breaker or subsequent breakers, the main energy dissipation occurs in a frequency range higher than the dominant frequency. This energy loss plays a significant role in increasing the energy of free waves. Moreover, a potential link between the number of carrier waves and wave breaking phenomena has been found. As the number of carrier waves increased, both the nonbreaking and breaking energy dissipation rates exhibited an overall increasing trend. The amount of nonbreaking energy dissipation was generally more than twice the breaking energy dissipation rate. For wave groups with more carrier waves, the modulation instability plays a significant role in generating larger waves. Furthermore, an analysis of the dominant frequency variations of the wave group before wave breaking suggests that wave breaking is not a sufficient condition for a frequency downshift in the wave spectra.

Shifting ceria’s function from inhibitor to promotor by oxygen vacancies - Hongfei Lin; Haibin Yin; Bo Wu; Hongliang Li; Jie Zeng (Science Bulletin, 2024)

Strong adsorption enhanced nitrogen removal from landfill leachate by PVA/CMC/WPU pellets immobilized microorganisms - Jiahui Tan; Yunshuang Hu; Chong Ding; Yuyu Li; Yufei Gu; Zhixia Li; Hongfei Lin (Journal of Water Process Engineering, 2024)

Effect of High Magnesium and Astragaloside IV on Vascular Endothelial Cells - Hongfei Qi; Teng Ge; Kun Wang; Jing Wang; Lin Dang; Juane Li; Haifang Wang (Cell Biochemistry and Biophysics, 2024)

Regulation of photoassimilate transportation and nitrogen uptake to decrease greenhouse gas emissions in ratooning rice with higher economic return by optimized nitrogen supplies - Jingnan Zou; Hailong Xu; Chaojie Lan; Bin Qin; Jinying Li; Witness Joseph Nyimbo; Hongmei Lin; Ziqin Pang; Nyumah Fallah; Chunlin Guo; Changxun Fang; Zhixing Zhang; et al. (Field Crops Research, 2024)

Erratum to: Transcriptome profiling and RXR gene family identification reveals the molecular mechanism of rapid aging after spawning of cuttlefish Sepiella japonica - Zhenyu Dong; Jiemei Zhao; Feng Guo; Shuangrui Lin; Huai Yang; Yingying Ye; Changfeng Chi; Hongfei Li; Baoying Guo (Journal of Oceanology and Limnology, 2024)

Transcriptome profiling and RXR gene family identification reveals the molecular mechanism of rapid aging after spawning of cuttlefish Sepiella japonica - Zhenyu Dong; Jiemei Zhao; Feng Guo; Shuangrui Lin; Huai Yang; Yingying Ye; Changfeng Chi; Hongfei Li; Baoying Guo (Journal of Oceanology and Limnology, 2024)

Efficient fluoride removal using nano MgO: mechanisms and performance evaluation - BoWen Liu; Li Ai; Ming Lei; Hongfei Lin (Environmental Science and Pollution Research, 2024)

Origin and geological significance of the first discovered seafloor oil seepage in the Beikang Basin, southern South China Sea - Wei Huang; Hongfei Lai; Zhifeng Wan; Wei Zhang; Miaomiao Meng; Jiujing Shang; Jinqiang Liang; Mengjie Xu; Lin Lin (Journal of Asian Earth Sciences, 2024)

Bacterial carbonic anhydrase-induced carbonates mitigate soil erosion in biological soil crusts - Zhimao Mai; Qiqi Chen; Lin Wang; Jian Zhang; Hao Cheng; Hongfei Su; Si Zhang; Jie Li (Journal of Environmental Management, 2024)

Self-assembly kieselguhr-based ZSM-5 for catalytic pyrolysis of mask waste to produce high value-added aromatics - Yufei Gu; Hucheng Ge; Yuke Liu; Qi Wei; Tianhua Gao; Hengshuo Gu; Hongbing Fu; Fuwei Li; Hongfei Lin; Lei Miao; Zhixia Li (Fuel, 2024)

Slow-release fertilizer deep placement increased rice yield and reduced the ecological and environmental impact in Southeast China: A life-cycle perspective - Chaojie Lan; Jingnan Zou; Jinying Li; Hailong Xu; Weiwei Lin; Peiying Weng; Changxun Fang; Zhixing Zhang; Hongfei Chen; Wenxiong Lin (Field Crops Research, 2024)

Targeting Ferroptosis Promotes Functional Recovery by Mitigating White Matter Injury Following Acute Carbon Monoxide Poisoning - Shuhong Wang; Binyuan Xiong; Yin Tian; Quan Hu; Xuheng Jiang; Ji Zhang; Lin Chen; Ruilie Wang; Mo Li; Xin Zhou; Tianxi Zhang; Hongfei Ge; et al. (Molecular Neurobiology, 2024)

Transcriptome analysis reveals tissue-specific responses of Mytilus unguiculatus to Vibrio alginolyticus infection - Hongfei Li; Jiemei Zhao; Yaru Li; Zhenyu Dong; Shuangrui Lin; Baoying Guo; Pengzhi Qi (Fish & Shellfish Immunology, 2024)

Verification of solitary wave numerical simulation and case study on interaction between solitary wave and semi-submerged structures based on SPH model - Jinbo Lin; Lili Hu; Yanli He; Hongfei Mao; Guanglin Wu; Zhenglin Tian; Dandan Zhang (Frontiers in Marine Science, 2023)
Due to significant influence on the safety of marine structures, the interaction between extreme waves and structures is a crucial area of study in marine science. This paper focus on the verification of a solitary wave meshless SPH model and the application of the model on the interaction between solitary waves and semi-submersible structures. A solitary wave propagation model is established based on the SPH method combined with Rayleigh solitary wave theory, quintic kernel function, artificial viscosity, and Symplectic Method. The accuracy of the model is validated by comparing the calculated wave height with the theoretical value. The calculated results with relative particle spacing H 0 / d 0 ≥ 20 are in good agreement with the analytical solution. The simulated solitary wave is also quite stable with a maximum L 2 error 0.016. Therefore, the proposed SPH model can accurately simulate the propagation of the solitary waves. A case study on the interaction between solitary waves and semi-submersible platforms is conducted. The results show that the interaction between solitary waves and semi-submersible causes two double peaks with wave heights of 0.398 m and 0.410 m, respectively, induced by overtopping at the center of the platform. The wave transmission coefficient K t is 0.880 due to that the solitary wave height reduces from 0.498 m to 0.438 m after the solitary wave propagates through the semi-submersible structure. In addition, the solitary wave induces significant vertical wave loads of the structure with a load amplitude of 0.688, while horizontal wave loads are relatively small with a load amplitude of 0.089. The solitary wave arrived the structure induces the upstream and downstream overtopping and forms a hydraulic jump leading to the complex flow field. The maximum velocity at the top and bottom of the structure is 2.2 m/s and 0.8 m/s respectively. Positive or negative vortex are formed at the bottom of the leading edge, top and downstream of the structure with the maximum intensity 28 s -1 and -40 s -1 . In a word, the meshless SPH model can conveniently and accurately simulate the propagation of the solitary waves, and be applied to the investigation of the wave height, velocity, vorticity, wave load, and wave breaking of the interaction between solitary waves and structures in ocean engineering.

Transcriptome profiling reveals the strategy of thermal tolerance enhancement caused by heat-hardening in Mytilus coruscus - Zhenyu Dong; Hongfei Li; Youji Wang; Shuangrui Lin; Feng Guo; Jiemei Zhao; Ronghui Yao; Li Zhu; Weifeng Wang; Isabella Buttino; Pengzhi Qi; Baoying Guo (Science of The Total Environment, 2023)

Convergence of soil bacterial communities with time and reduction of bacterial interaction complexity in response to meso- and microplastic stress - Lin Yue; Yangbo Liu; Guanhui Li; Hui Deng; Yuanyuan Zhao; Dan Feng; Hongfei Sun; Huamei Yu; Chengjun Ge; Haiying Chen (Journal of Environmental Chemical Engineering, 2023)

The susceptibility of Hyphantria cunea larvae to microbial pesticides Bacillus thuringiensis and Mamestra brassicae nuclear polyhedrosis virus under Cd stress - Jinsheng Xu; Lin Zheng; Mingtao Tan; Hongfei Wu; Shanchun Yan; Dun Jiang (Pesticide Biochemistry and Physiology, 2023)

High-efficiency removal of Cs (I) by vermiculite/zinc hexacyanoferrate (II) composite from aqueous solutions - Tianya Dai; Jinpeng Feng; Jiann-Yang Hwang; Yangyang Bao; Chenhui Gao; Zeping Wang; Wei Mo; Xiujuan Su; Hongfei Lin (Journal of Environmental Chemical Engineering, 2023)

Interfacial oxygen coordination environment regulation towards high-performance Li-rich layered oxide cathode - Saichao Li; Yuanyuan Liu; Yinggan Zhang; Wei He; Hongfei Zheng; Weibin Guo; Hualong Wu; Guiyang Gao; Baisheng Sa; Laisen Wang; Qingshui Xie; Jie Lin; et al. (Chemical Engineering Journal, 2023)

An experimental study on nonlinear wave dynamics for freak waves over an uneven bottom - Yanli He; Guanglin Wu; Hongfei Mao; Hongzhou Chen; Jinbo Lin; Guohai Dong (Frontiers in Marine Science, 2023)
The effect of the non-uniform bathymetry on the nonlinear wave dynamics for the freak wave is investigated experimentally, with emphasis on the interrelations between different nonlinear behaviors resulting from various geometric parameters and spectral analysis. Both the frequency modulation and the nonlinear phase coupling can be provoked by the decreasing water depth and weakened after the top peak of the bar, the nonlinear exhibition for transferring energy to high-frequency contents over shoal supports that frequency modulation can reflect nonlinear phase coupling well. The consistent change of the Hilbert energy spectrum and the bicoherence shows that the main nonlinear interaction in the process of wave propagation in shallowing water is quadratic nonlinearity. In addition, the geometric study is conducted to investigate the effect of the water depth on the parametric variations, the research results show that the mean asymmetry and kurtosis change abruptly when the wave approaches the top peak of the bar. As the wave propagates along the water flume, freak waves can be generated at various locations, however, they appear more frequently as waves propagate close to the shallowest water depth, and the maximum probability of occurrence for a freak wave can be up to about 1%.

Quantifying the dynamic processes of soil erosion and lake sediment deposition in the Holocene in China - Hongfei Zhao; Yunhong Lin; Jie Zhou; Qianli Sun; Linhai Yang; Claudio O. Delang; Hongming He (Quaternary Science Reviews, 2023)

Defense response of Fraxinus mandshurica seedlings to Hyphantria cunea larvae under Cd stress: A contradiction between attraction and resistance - Shanchun Yan; Mingtao Tan; Lin Zheng; Hongfei Wu; Kai Wang; Rusong Chai; Dun Jiang (Science of The Total Environment, 2023)

Feasibility of reuse of modified electrolytic aluminium spent refractory material in asphalt and assessment of its environmental stability - Hao Tu; Xinyu Li; Yaseen Muhammad; Xin Jin; Hongfei Lin; Ruinan Pei; Zhenxia Zhao; Jing Li (Journal of Cleaner Production, 2023)

Catalytic co-cracking of biomass and waste plastics with sawdust mediated ZSM-5 synthesized via activating gel process - Fuwei Li; Xiaofeng Wang; Hengshuo Gu; Hongbing Fu; Asad Ali; Hongfei Lin; Zhixia Li (Fuel, 2023)

Eukaryotic plankton community assembly and influencing factors between continental shelf and slope sites in the northern South China Sea - Tangcheng Li; Guilin Liu; Huatao Yuan; Jianwei Chen; Xin Lin; Hongfei Li; Liying Yu; Cong Wang; Ling Li; Yunyun Zhuang; Lin Senjie (Environmental Research, 2023)

Proteomic analysis of the spineless cuttlefish Sepiella japonica: Exploratory analyses on the phenomenon of death after spawning - Hongfei Li; Shuangrui Lin; Pengzhi Qi; Jingtian Wang; Meihua Fan; Hongwei Huang; Zhenyu Dong; Kaida Xu; Baoying Guo (Frontiers in Marine Science, 2022)
To better understand the physiological events involving death after spawning in S. japonica (Japanese spineless cuttlefish), we have presently generated a proteomic data set to properly examine this phenomenon. As such, a proteomic-based approach was employed to identify differentially expressed proteins (DEPs) in the optic glands of S. japonica , at three distinct growth stages: pre-spawning after sexual maturity (group A); spawning (group B) and postspawning before death (group C). About 955, 1000, and 1024 DEPs were identified for each comparative group analysis (i.e., group B vs A, group B vs C, and group C vs A). We further discovered that the function of these newly identified DEPs was mostly related to molecular events such as gene translation and signal transduction. According to the enriched GO terms obtained by Gene Ontology analysis, the function of most DEPs was correlated with structural molecule activity, ribosome function and gene expression. The majority of DEPs were known to be involved in signal transduction and energy metabolism, interestingly, some aging-related DEPs were also identified. Putting together, our study provides new insights, at the protein level, in the phenomenon of death after spawning in S. japonica , by referring to anti-aging effects conserved in other cephalopoda species.

MiR-361-3p alleviates cerebral ischemia–reperfusion injury by targeting NACC1 through the PINK1/Parkin pathway - Xihong Ye; Hua Song; Huimin Hu; Chunli Zhou; Qinyi Chen; Lin Hong; Min Huang; Hongfei Zhu (Journal of Molecular Histology, 2022)

Prussian blue modified CeO2 as a heterogeneous photo-Fenton-like catalyst for degradation of norfloxacin in water - Ruyi Xiao; Yuanyuan Zhang; Shuangfei Wang; Hongxiang Zhu; Hainong Song; Guoning Chen; Hongfei Lin; Jian Zhang; Jianhua Xiong (Environmental Science and Pollution Research, 2021)

Epidemiological and phylogenetic analysis of canine kobuviruses in Tangshan, China - Zhaoyang Wang; Yajun Jiang; Xueting Liu; Weidong Lin; Qianqian Feng; Ting Xin; Xiaoyu Guo; Shaohua Hou; Hongfei Zhu; Hong Jia (Archives of Virology, 2020)

The degradation of BPA on enhanced heterogeneous photo-Fenton system using EDDS and different nanosized hematite - Xiaoqing Feng; Mengqi Luo; Wenyu Huang; Ying Huang; Hongjie Xie; Zisong Xu; Jian Zhang; Wei Luo; Shuangfei Wang; Hongfei Lin (Environmental Science and Pollution Research, 2020)

Imaging study of pseudo-CT images of superposed ultrasound deformation fields acquired in radiotherapy based on step-by-step local registration - Hongfei Sun; Tao Lin; Kai Xie; Liugang Gao; Jianfeng Sui; Xinye Ni (Medical & Biological Engineering & Computing, 2019)

Effect of Low-Intensity Pulsed Ultrasound on MMP-13 and MAPKs Signaling Pathway in Rabbit Knee Osteoarthritis - Xueping Li; Jianan Li; Kai Cheng; Qiang Lin; Daxin Wang; Hongfei Zhang; Hengyuan An; Mingxia Gao; Anliang Chen (Cell Biochemistry and Biophysics, 2011)